Risk Factors and Comorbidities in Young Indian Patients with Hypertension: REAL YOUNG (Hypertension) Study - Desai, Nagaraj; Unni, Govindan; Agarwala, Rajeev; Salagre, Santosh; Godbole, Sanjay; Dengra, Ashish; Abhyankar, Mahesh V; Revankar, Santosh (Integrated blood pressure control, 2021)
To analyze the risk factors and comorbidities among the young Indian adults with hypertension. This was a retrospective, multicentric real-world study which included patients diagnosed with and receiving treatment for hypertension. Data were collected from the medical records of clinics/hospitals across 623 study sites in India. Patients of either sex and aged 18-45 years were included. Demographic details (age, sex, anthropometric measurement), medical and family history, sedentary lifestyle, smoking status and alcohol consumption data were extracted. Descriptive and comparative analysis (Mann-Whitney and chi-squared test) was done. Out of 15,006 young patients diagnosed with hypertension (men=63.6%), 65.7% belonged to the age group of >35-45 years. The median body mass index was 27.0 kg/m . Patients diagnosed with only hypertension were 29.1% while other predominant comorbidities with hypertension were diabetes mellitus (42.4%) and dyslipidemia (7.8%). Hypertension with diabetes mellitus were prevalent in the age group of >35-45 years (43.8%). More than half of the patients with hypertension (n=7656) had a sedentary lifestyle. Overall, 35.6%, 47.3%, and 56.7% of the patients were alcoholic, smokers (present and former), and had a family history of hypertension, respectively. The results showed that among the young population, hypertension was common in the age group of >35-45 years and diabetes mellitus and dyslipidemia were common comorbidities. Family history, sedentary lifestyle, smoking, alcohol consumption, and body mass index may also contribute to hypertension.